ESG AND UNDERWRITER REPUTATION IN IPO UNDERPRICING: A SYSTEMATIC LITERATURE REVIEW WITH COVID-19 CONTEXT - Heltyani, Wayan Eka; Wardhana, Putu Ariesta Pradasari (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
Underpricing in Initial Public Offerings (IPOs) remains a prominent anomaly in global corporate finance, particularly during systemic shocks such as the COVID-19 pandemic. This study employs a Systematic Literature Review (SLR) of 50 peer-reviewed articles published between 2005 and 2025 to investigate the influence of Environmental, Social, and Governance (ESG) disclosure and underwriter reputation on IPO pricing, while assessing the moderating effect of the pandemic. The review reveals that transparent and standardized ESG disclosure functions as an effective non-financial signal that reduces information asymmetry and lowers underpricing. Similarly, reputable underwriters enhance investor confidence and issuer credibility, although their effectiveness is context-dependent and may decline in overheated markets or when reputational capital is exploited opportunistically. The pandemic intensified investors reliance on credible quality indicators, underscoring the critical role of ESG and underwriter reputation in stabilizing expectations under high uncertainty. Nonetheless, key research gaps persist, including the absence of standardized ESG metrics, the scarcity of longitudinal studies covering pre- and post-crisis dynamics, and the limited use of integrated models addressing both mediation and moderation mechanisms. Future research directions highlight the need for cross-disciplinary approaches, such as big data analytics and natural language processing, to refine the measurement of ESG perceptions. This study contributes by extending theoretical insights into signaling mechanisms in IPO pricing and offering practical implications for issuers, underwriters, and regulators operating in volatile market conditions.